The ichthyology collection at the Natural History Museum of El Salvador (MUHNES): Species checklist and new country records - González-Murcia, Saúl; Álvarez-Calderón, Francisco Samuel; Alvarado-Larios, Raquel; Marín-Martínez, Cindy Marlene; Angulo, Arturo (Zootaxa, 2019)
The ichthyology collection at the Natural History Museum of El Salvador (MUHNES) was established in 1970. Herein, we provide the first quantitative and qualitative description of the collection; and the first public record of the specimens and taxa therein represented. The MUHNES fish collection is the largest and most important of El Salvador, hosting 3791 specimens in 1005 lots representing 26 orders, 75 families, 159 genera and 248 species from both marine and freshwater environments, including larval, juvenile and mainly adult specimens. MUHNES specimens include 39% of the 587 species reported in the official national checklist of fishes of El Salvador, and support the inclusion of 47 additional species for a new total of 634. Furthermore, MUHNES specimens support (1) the occurrence of Cathorops fuerthii along the coast of El Salvador, extending its distribution from northern Costa Rica; (2) the occurrence of Atherinella starksi in El Salvador, reducing a gap for records between Nicaragua and México and (3) the extension in the distribution range of Profundulus kreiseri to Morazán, El Salvador. This study represents an advance on the understanding of diversity and distribution of the national ichthyofauna.